Tracking chamber made of 15-mm mylar drift tubes. (11th May 2017) - Kozhin, A.; Borisov, A.; Bozhko, N.; Fakhrutdinov, R.; Plotnikov, I.
Abstract: We are presenting a drift chamber composed from three layers of mylar drift tubes with outer diameter 15 mm. The pipe is made of strip of mylar film 125 micrometers thick covered with aluminium from the both sides. A strip of mylar is wrapped around the mandrel. Pipe is created by ultrasonic welding. A single drift tube is self-supported structure withstanding 350 g wire tension without supports and internal overpressure. About 400 such tubes were assembled. Design, quality control procedures of the drift tubes are described. Seven chambers were glued from these tubes of 560 mm length. Each chamber consists of 3 layers, 16 tubes per layer. Several chambers were tested with cosmic rays. Results of the tests, counting rate plateau and coordinate resolution are presented.